(untitled) (Revista Apotheke, 2022)
Women are victims of numerous forms of discrimination and violence in our society. Therefore, it is imperative to develop strategies to sensitize society about these problems, which can contribute to the transformation of mentality necessary to effectively face them. Based on the problematization of art and its history, we have outlined and carried out educational actions with the following objectives: to stimulate a reflexive and critical attitude about gender relations and to encourage the opposition and the fight against discrimination and violence against women. These actions were conceived in order to elucidate, from the discussion about works, artists and the art system, that gender prejudices, asymmetries and violence have been trivialized and reinforced, but also exposed and fought through art over the course of history. The statements of the participants of these actions show that the proposed problematizations have aroused new ways of seeing, fostering important reflections and discussions about the stereotyping, exclusion and violence suffered by women, inside and outside the field of art.